Pemberdayaan Ibu-Ibu PKK Desa Muara Jernih Melalui Pelatihan Motif Batik Modern - Hendriyaldi; Erida; Syaparuddin; Musnaini; Setiawan, Wahyu Juari (Studium: Jurnal Pengabdian Kepada Masyarakat, 2024)
Muara Jernih Village holds significant potential for creative economy development through its local batik craftsmanship. However, batik artisans in this village face various challenges, such as a lack of innovation in motif design, limited knowledge of modern dyeing techniques and marketing, low product quality, and restricted market access. These conditions hinder efforts to empower the community economically and preserve the local batik culture. This community service activity aims to enhance the knowledge and skills of the PKK women in Muara Jernih Village in designing modern batik motifs, improving product quality, expanding market access, empowering the creative economy, and preserving the local batik heritage. The solutions provided include training in modern batik motif design, digital marketing and branding workshops, and business development mentoring. This approach is expected to address the challenges faced by batik artisans and promote the sustainability of the creative economy in Muara Jernih Village.